Research on Steel Slag Resin Mixture Used in Rapid Repair of Pavement Damage. Issue 3 (April 2021) - Han, Yafang; Wu, Di; Xu, Jie; Liao, Zhike; Sun, Yangyong
Abstract: In order to explore the pavement performance of steel slag for pavement damage repair, steel slag, river sand and resin binder are mixed in proportion to prepare steel slag mixture. The test results show that the steel slag mixture has excellent high temperature stability, water stability, low water absorption and low expansibility. The engineering application shows that the steel slag resin mixture has no quality problem after being used to repair the pavement damage for half a year. At the same time, it can also solve the problem of environmental pollution caused by the solid waste of steel slag, which has good social benefits.